2016
DOI: 10.1016/j.conbuildmat.2015.12.111
|View full text |Cite
|
Sign up to set email alerts
|

High strength mortars using ordinary Portland cement–fly ash–fluid catalytic cracking catalyst residue ternary system (OPC/FA/FCC)

Abstract: h i g h l i g h t s An important nucleation effect was attributed to FA at early hydration age. An early age pozzolanic effect was developed by FCC. High strengths were achieved in binary (OPC/FA) and ternary systems (OPC/FA/FCC). Strength contributions (nucleation, hydration, pozzolanic) were calculated. The synergic role of the combination of both pozzolans was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 40 publications
1
15
0
2
Order By: Relevance
“…However, synergetic effects of the different pozzolan application were not studied by Le et al 23 and no comparisons with the binary binders were done. The results obtained in this paper were, as for the synergy, in a qualitative agreement also with Soriano et al 24 which was, supposedly, due to the approximately 10% CaO content in the applied fly ash.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, synergetic effects of the different pozzolan application were not studied by Le et al 23 and no comparisons with the binary binders were done. The results obtained in this paper were, as for the synergy, in a qualitative agreement also with Soriano et al 24 which was, supposedly, due to the approximately 10% CaO content in the applied fly ash.…”
Section: Discussionsupporting
confidence: 92%
“…Le et al proposed, as a result of a relatively complex design procedure, several concrete mixtures based on ternary cements with the Portland cement:fly ash:rice husk ash and Portland cement: fly ash: silica fume ratio of 7:2:1 and achieved f c of 120 MPa after 28 days. Soriano et al on the other hand, reported a very substantial synergy achieved using the Portland cement‐fly ash‐spent fluid catalytic cracking catalyst (FCC) binder with a 7:2:1 ratio. The application of FCC led to approximately 20% improvement in f c , as compared with the 7:3:0 and 10:0:0 binders, with the best f c value of 97 MPa after 28 days.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the dilution effect and slow pozzolanic reaction, FA has an adverse effect on the early-age strength of mortar. The early-age strength goes down for a cement replacement by FA in the range of 10%-70% [24,26,[28][29][30]43,89,160]. The use of 40% FA causes a 34% decrease in the 28-day tensile strength of mortar [26].…”
Section: Effects On Strengthmentioning
confidence: 99%
“…The strength gap between the mortar with OPC alone and the mortar with binary FA-OPC binder decreases with age. In some studies, it took 90 days to show a similar or better strength compared to the control mortar [28,29]. Other investigations have shown that it took a longer time to gain a similar strength [26,43].…”
Section: Effects On Strengthmentioning
confidence: 99%
“…The widest use of fly ash is in the production of cement because it exhibits pozzolanic properties [3,4]. Most international and domestic research is based on the use of fly ash as a substitute for cement in concrete production [5][6][7][8]. Mohanty and Patra [9] conducted dynamic testing for construction of embankments made of fly ash.…”
Section: Introductionmentioning
confidence: 99%